The Image and culture of the UP CMC and its role on the emergence of change in the social behavior of its students - Santiano, Abigail R. 1977-; Paragas, Fernando DL Cruz; dela Cruz, Marichelle S.D.; University of the Philippines Diliman College of Mass Communication (Quezon City College of Mass Communication, University of the Philippines Diliman, 2000)
Each person has a highly organized belief-attitude-value system which guides their behavior. This is basically the idea behind Rokeach's theory on Beliefs, Attitudes and Values. This theory guided the proponent of the study as she investigated the relationship between CMC students' perception on the image and culture of CMC and the emergence of change in their social behavior. The research employed a one-shot survey method, gathering pertinent data among a randomly drawn sample of one hundred students of the College of Mass Communication. Certain quantitative techniques were utilized to organize and interpret the gathered data. Percentage Distribution Tables were utilized for data presentation. Cross Tabulations facilitated the investigation of variable relationship. The results showed that CMC students generally perceive the image and culture of their college positively, and at the same time they think that the students in CMC are different from other UP students. Remarkable observations of respondents were that CMC students are more fashionable, more confident and more creative as compared to other UP students. A big majority of the respondents admitted that they have experienced some changes in their social behavior. The trend is that when students perceive CMC positively, the more they experience change in their social behavior. Students who have been in CMC for at least two years become more confident in expressing themselves and become friendlier with strangers. The chi-square test showed that there is a significant relationship between students' perception on their college and their social behavior changes.
Vita.
Thesis (A.B. Communication Research)--University of the Philippines Diliman
Keywords: Interpersonal relations -- Philippines